Habitat suitability, niche unfilling and the potential spread of Pterois miles in the Mediterranean Sea. (May 2020) - Poursanidis, Dimitris; Kalogirou, Stefanos; Azzurro, Ernesto; Parravicini, Valeriano; Bariche, Michel; zu Dohna, Heinrich
Abstract: The common lionfish Pterois miles has rapidly spread across the eastern Mediterranean Sea. We compiled occurrence data from both native and invaded range under the framework of Species Distribution Modelling (SDM). Through a construction of an environmental suitability model and estimation of spread rates we investigated the lionfish climate niche in both its native and invaded domains, this latter represented by the Mediterranean region. Model projections allowed to identify suitable areas for lionfish establishment in the Mediterranean. Spread analysis suggested that a further geographical expansion in this basin could be completed within the next years. Our results did not provide evidence for niche expansion but highlighted a high degree of niche unfilling thus prospecting a likely spread of Mediterranean lionfish invasion beyond the predictions of current SDMs. These findings provide novel inputs to forecast the future geographical evolution of the lionfish in the Mediterranean Sea and asses the related risk of invasion. Highlights: The lionfish has an ongoing invasion and can reach until Gibraltar in the next 5 years. The incomplete invasion makes SDM to fail predicting the full potential of spread. Invasive SDM has to include data from both the native range and invasive area.